2018
DOI: 10.1016/j.asjsur.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of the decellularized tracheal allograft in animal model (rabbit)

Abstract: Complete regeneration of epithelium and cartilage tracheal rings occurred after the implantation of decellularized tracheal allografts without immunosuppression. We demonstrate that the decellularized process reduces the allogeneic response to the trachea. Therefore, we believe that the decellularized tracheal allograft is an excellent choice for tracheal replacement. To our knowledge, this is the first study to observe the long-term (1 year) prognosis of this transplanted trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The immunological rejection of tracheal grafts has been the biggest obstacle to the success of tracheal replacement, and its immunogenicity is mainly derived from the epithelial and mucosal lamina propria. 25,27,28 Decellularization technology can effectively dissolve epithelial and mucosal cells in natural trachea through detergents and enzymes, remove the immunogenicity of the matrix, and eliminate the need for immunosuppressive agents to reduce rejection after surgery. 9,10 Studies have shown that nonchondral cells, such as those in the epithelium, interstitium, and muscle of the tracheal matrix of rabbits, are completely eliminated by seven DEM cycles, and MHC-II antigens are removed.…”
Section: Discussionmentioning
confidence: 99%
“…The immunological rejection of tracheal grafts has been the biggest obstacle to the success of tracheal replacement, and its immunogenicity is mainly derived from the epithelial and mucosal lamina propria. 25,27,28 Decellularization technology can effectively dissolve epithelial and mucosal cells in natural trachea through detergents and enzymes, remove the immunogenicity of the matrix, and eliminate the need for immunosuppressive agents to reduce rejection after surgery. 9,10 Studies have shown that nonchondral cells, such as those in the epithelium, interstitium, and muscle of the tracheal matrix of rabbits, are completely eliminated by seven DEM cycles, and MHC-II antigens are removed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of lung tissue and the need for instant functionality of used implants, a lung's dECM requires recellularization with epithelial and endothelial cells via cell infusion and bioreactors for ex vivo generation, maturation, and maintenance of the so-called bioartificial lungs. In vivo implantation of these organs in rats yields anastomosis, but long-term success is still to be achieved [143,144].…”
Section: Tissues Related To Respiratory Systemmentioning
confidence: 99%
“…The updates in creating tracheal grafts have been demonstrated through protocol improvements in physical decellularization, chemical decellularization, and bioreactor methods in the past five years. [73][74][75][76][77] These protocol advancements have also been seen in other organ systems using animal-based models such as esophagus (murine-rat), 78 lung (ovine), 79 cartilage (porcine), 80 uterus (ovine and leporine), 81,82 bladder (leporine), 83 pericardium (bovine), 84 submillimeter vasculature (murine-rat), 85 and intestine (murine-mouse) 86 model tissues. Protocol advancement in the field of vasculature has been especially important given this is often viewed as a challenge due to the size and difficulty of reseeding these grafts with endothelial cells.…”
Section: History and Development Of Decellularization For Bioenginementioning
confidence: 85%
“…Institution of a protocol to accomplish ingrowth of multiple cell types may be the key to creating implant‐ready grafts. The updates in creating tracheal grafts have been demonstrated through protocol improvements in physical decellularization, chemical decellularization, and bioreactor methods in the past five years 73–77 . These protocol advancements have also been seen in other organ systems using animal‐based models such as esophagus (murine‐rat), 78 lung (ovine), 79 cartilage (porcine), 80 uterus (ovine and leporine), 81,82 bladder (leporine), 83 pericardium (bovine), 84 submillimeter vasculature (murine‐rat), 85 and intestine (murine‐mouse) 86 model tissues.…”
Section: Extracellular Structural Matrix Functionsmentioning
confidence: 99%